Suggested Solutions for Sleep Problems in Children with Intellectual Disabilities and Their Mothers - Çiğdem Müge Haylı (Türk Uyku Tıbbı Dergisi, 2022)

(untitled)
Similar to essential air, water, and food, sleep is a basic physiological requirement for all living beings. Sleep is essential for growth and development in children. Sleep problems are considered to be a major challenge in physiological, psychological, and social dimensions, especially for children with intellectual disabilities as well as their mothers. Therefore, understanding and taking appropriate measures is necessary to address sleep problems that negatively affect these children and their mothers. This review aimed to identify sleep problems and provide solutions for children with intellectual disabilities and their mothers.